The Level of Effectiveness of Social Upbringing Methods in Promoting Public Taste of Saudi Society (An Applied Study on a Sample of Male and Female Teachers in the City of Dammam in the Eastern Region of Saudi Arabia) - Alqahtani, Albanderi Saad; Mejri, Olfa Ahmed (Journal of Humanities & Social Sciences, 2023)
The study aimed to identify the level of effectiveness of socialization methods in promoting public taste in Saudi society, and to achieve this, the study relied on the social junction curriculum, and the questionnaire was used to collect data, as the study was applied in the city of Dammam in the eastern region, and the number of the sample reached (289) teachers and the results showed the importance of the method of following the example, as one of the most important methods of socialization for male and female teachers, followed by the method of guidance, then the method of reinforcement, and finally the method of punishment when the desired methods do not succeed in enhancing behavior, and the study revealed the high level of effectiveness of upbringing methods in promoting public taste with respect for customs and traditions, teachers and teachers provide advice and guidance, and they are enhanced by societal values, customs and traditions of society, and they urge to wear correct dress, and they enhance the appreciation of the elderly, and the high level of effectiveness of the methods of upbringing in promoting public taste in dealing with public places, it is clear that teachers urge students to preserve public property, enable the value of discipline and follow -up, and are interested in developing ethical behaviors, and shows the high level of effectiveness of the methods of upbringing in enhancing public taste by dealing with others, as teachers strengthen non -interference in the privacy of others, the importance of helping them, and taking into account the feeling of dealing with them, and encourage to request permissions, and the share of salutations and handshake. While the most prominent recommendations of the Ministry of Education came to enrich the activities with awareness lectures to enhance public taste with the help of experts, enriching the curricula by rooting public taste, and the need for teachers to contribute to clarifying the public taste rules, and establishing courses that urge to enhance public taste in Saudi society.